Możliwości uniknięcia zdegenerowanych rozwiązań w analizie unfolding przy wykorzystaniu algorytmu PREFSCAL - Zaborski, Artur (Possibilities of Avoiding Degenerate Solutions in Unfolding Analysis by Using PREFSCAL Algorithm, 2009)
The article presents PREFSCAL algorithm in which avoiding degeneracy in multidimensional unfolding is possible by modification of the loss function. In the structure of STRESS function, the variation coefficient is used as a diagnostic for identifying solutions with constant interpoint distances. Finally, empirical data set was analyzed by PREFSCAL method to show the benefits of the modification of the loss function. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 275-282